Conservative management of subglottic stenosis in pregnancy resulting in vaginal birth. (3rd April 2014) - Nash, Zachary; Krishna, Archana; Darwish, Mohamed; Mascarenhas, Lawrence
Abstract : We present a case of subglottic stenosis complicating pregnancy. The patient was born prematurely at 24 weeks gestation and required a twelve-month period of intubation. Airway trauma from prolonged intubation resulted in acquired subglottic stenosis. As an adult the patient had a longstanding audible stridor; however, was not breathless during activity before or during pregnancy. The patient went into spontaneous labour at 37+4 weeks and delivered vaginally with epidural analgesia. This case is significant, as no cases of a patient with such a degree of stenosis delivering vaginally without airway treatment have been reported.